The performance of phototherapy in angiogenesis and tissue repair (Research, Society and Development, 2021)
Wound healing is a complex process, composed of several interdependent and simultaneous stages to repair the tissue and, among the methods used, laser therapy has biological and regenerative stimulatory effects. The aim of this review is to understand the mechanism of action of laser therapy in tissue repair and, more specifically, angiogenesis. A bibliographic search was performed in the databases PUBMED, LILACS and SCIELO on the subject, using the following keywords: "phototherapy and angiogenesis" and "phototherapy and wound healing". In this search, 3634 articles were totaled, which after analysis of the criteria, 3624 were excluded, remaining 10 papers. In view of the above, it can be concluded that laser therapy has been presented as a therapeutic alternative in tissue repair, acting as a photobiomodulator, with analgesic, anti-inflammatory, anti-edema and antimicrobial effects, offering improvements in cellular response mechanisms and presenting advantages in the three stages of the healing process.